341
Hari Shankar
·2010-02-05 07:39:14
Well \sum_{k=0}^n \binom{n-k}{k} is the expression for the nth Fibonacci number.
So fn is the nth Fibonacci number.
And we have the recursion f_{m+2} = f_{m+1} + f_m
So by R_3 \rightarrow R_2+R_3 you can make two rows identical and so the determinant is zero
1
Che
·2010-02-05 09:49:25
thanks
btw
this \sum_{k=0}^{n}\binom{n-k}{k} means nth Fibonacci number.........din knew that
i was thinking it to be (n-k)Ck :P
341
Hari Shankar
·2010-02-05 17:39:47
I think you have misunderstood. That isnt a representation.
\sum_{k=0}^n ^{n-k}C_k = f_n where fn is the nth Fibonacci number